Study of Ciliate Commensals from the Gills of Freshwater Bivalves (Molluscs: Bivalvia) of Jayakwadi Dam, Paithan, (M.S.), India - and S. V. Nikam, N. Z. Deshmukh*, B.V. More, E. L. Jaid (Journal of Ecobiotechnology, 2011)
Samples of bivalve species viz. Lamillidens marginalis L. corrianus and Indonaia caeruleus were collected from the Jayekwadi dam. Three species of obligate commensalistic ciliates, Conchophthirus acuminatus, C. curtus and C. nikamentus n.sp. belonging to genus Conchophthirus were observed on the gills and mantle cavity of bivalve. Prevalence of the ciliate infection were reported for all three species of bivalves and Conchophthirus.Ã‚Â  Correlation of infection intentisity with the length of shell in three species of bivalves were studied.